Equestrian statue of King Edward VII - Ghosh, Ayan (2023)
Edward VII (1841–1910) was the King of the United Kingdom and Emperor of India, from 1901 until his death in 1910. His equestrian statue earlier stood at Kala Ghoda, which got named after the black (kala) horse (ghoda). In August 1965, the statue was dismounted from its plinth and shifted to Jijamata Udyan. The plinth is displayed at the Bhau Daji Lad Museum.